The phenomenon of self-healing among people over 65 in the Lublin region - Rudnicka-Drożak, Ewa; Szymuś, Magdalena; Jankowska, Paula; Jankowski, Krzysztof (Journal of Education, Health and Sport, 2018)
Introduction Self-medication is a phenomenon that has been accompanying people for centuries. Nowadays, it is gaining strength due to increasing health awareness and greater availability of medicines. Self-medication significantly relieves the public health care system and can be considered as a positive phenomenon of public health. However, it involves threats such as polypharmacy, drug interactions or delayed diagnosis of serious diseases, especially dangerous for the elderly. Objective The aim of this study was to assess the occurrence of self-healing among patients of one of Lublin’s hospitals and their determinants. Material and methods The research was carried out between May and August 2014 among 140 aged over 65 years patients of Hospital of Jan of God in Lublin and members of their families. The study used methods s diagnostic survey and a questionnaire constructed by the authors. The obtained results were subjected to statistical analysis using the STATISTICA 13.0 program. Significance of intergroup differences was verified using the Pearson Chi-square test. Results 79.29% of respondents admitted that they buy over-the-counter drugs. The ailments that were the cause of self-medication were the common cold (32.14%), pain (29.29%), weakness of the body (19.29%), gastrointestinal complaints (12.14%) and inflammation of the upper respiratory tract ( 9.29%). Conclusions Self-medication among seniors is a very common phenomenon. Nearly half of the seniors surveyed change their medical recommendations, most often shortening the time of using drugs only to relieve symptoms or taking medications selectively. Therefore, there is a need for intensive education of patients regarding self-medication with the use of over-the-counter drugs.